Bioactive extract having blood anticoagulant activity. - Abdullah, Janna Ong; Hamid, Muhajir; Sieo , Chin Chin; Seman, Zainina; Mohd Tohit, Eusni Rahayu; Manicam, Caroline (2008)
The present invention relates to the anticoagulant activity of the crude aqueous extract of Melastoma malabathricum Linn. on normal human blood. Consequently, this extract can be developed into an oral anticoagulant drug for human consumption. Anticoagulant activity of this extract is evaluated in terms of prolongation of clotting time in seconds in comparison to normal human blood clotting time as well as with commercially available oral anticoagulant drug, warfarin.